PERMASALAHAN HUKUM BARU DALAM PELAKSANAAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (STUDI KASUS KOTA PALU) - Dewi Kemala Sari (Hang Tuah Law Journal, 2023)
The issue of land acquisition for the public interest has always caused polemics. Every land acquisition activity for development always triggers dissatisfaction and helplessness in the people affected by the development project. A new legal problem in implementing land acquisition for the construction of the Lalove Bridge in Palu City is the suspicion of corruption cases in land acquisition activities involving authorized officials and landowners. Based on this description, the problem formulation that becomes the focus of this research is the problem of alleged corruption cases in implementing land acquisition in Palu City. This research uses empirical juridical research methods, namely analysis obtained from experience, observations based on field data and information obtained from direct interviews with various sources and agencies related to this research. The alleged corruption of land acquisition for the construction of Palu's Lalove Bridge implies that new problems in the implementation of land acquisition for development in the public interest are very prone to taking advantage, and there can also be a misappropriation of positions of elements of the relevant agencies.